Analisis Perlindungan Hukum terhadap Hak Kesejahteraan Sosial Pedagang Kaki Lima di Kelurahan Sempakata Kecamatan Medan Selayang Berdasarkan Perda Nomor 5 Tahun 2022 (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze efforts to implement legal protection for the social welfare rights of street vendors based on Regional Regulation Number 5 of 2022 and to analyze the obstacles faced in implementing regional regulations related to the protection of social welfare rights of street vendors. The research method used is qualitative research and descriptive research type, and uses a normative juridical approach to analyze regional regulations and an empirical juridical approach to explore real conditions in the field. The subjects of this study were Street Vendors and the Head of Public Order in Sempakata Village, Medan Selayang District. Data collection used is primary data and secondary data. Primary data in the form of observations and interviews, while secondary data in this study is legal literature, government policy documents such as regional regulations. Data analysis used the Miles and Huberman approach, namely data reduction, data presentation, and drawing conclusions. Based on the results of the study, it shows that legal protection for street vendors as regulated in Regional Regulation Number 5 of 2022 has not been fully realized in Sempakata Village. The implementation of this regional regulation, such as limited public awareness campaigns, the lack of suitable relocation sites, and the lack of empowerment programs, are major obstacles to its implementation. Although the regulation normatively includes social welfare rights, such as training, business assistance, and protection from eviction, in practice, these are still not optimally enjoyed by street vendors. This study recommends strengthening the role of local governments and sub-districts, improving cross-sectoral coordination, and adopting a more humane approach to managing street vendors to ensure the fair and sustainable fulfillment of their social welfare rights.